2015
DOI: 10.4236/ojepi.2015.52018
|View full text |Cite
|
Sign up to set email alerts
|

Current Status, and Correlates of Abortion among Rural Women of Gonji Kollela District, Northwest Ethiopia

Abstract: Background: Evidences indicate that unsafe abortion is one of the most important causes of maternal mortality in Ethiopia. Ethiopia strives to curb maternal mortality. Hence, current data on abortion, and its correlates are required. Objective: To assess the prevalence and associated factors of abortion among women of reproductive age (15-49 years) in rural kebeles of Gonji Kolela District. Methods: A community based cross-sectional study was conducted among randomly selected 611 women in six rural kebeles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Women with primary and secondary education had a considerably higher risk of having an induced abortion, according to the results of a pooled meta-regression analysis of eight studies [ 23 , 28 , 31 , 32 , 36 , 44 46 ] (AOR = 2.63, 95% CI: 1.7–4.06) ( Fig 8 ). There was some moderate heterogeneity across the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with primary and secondary education had a considerably higher risk of having an induced abortion, according to the results of a pooled meta-regression analysis of eight studies [ 23 , 28 , 31 , 32 , 36 , 44 46 ] (AOR = 2.63, 95% CI: 1.7–4.06) ( Fig 8 ). There was some moderate heterogeneity across the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, the largest sample size was 146,713, according to a study from the African nation of Congo [ 21 ]. Different authors conducted induced abortion studies in Ethiopia in different years, with the highest prevalence (68.7%) and the lowest prevalence (1.1%) [ 22 , 23 ]. The Newcastle-Ottawa Scale quality assessment criteria for each primary study’s quality score indicated no appreciable risk; hence, all the studies were considered in this systematic review and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This review included 33 studies conducted in various regions of Ethiopia. Of all the studies, 8 (24.24%) were from the Amhara Region,11 12 15 16 23–26 South Nations and Nationalities Peoples accounted for 9 (27.27%) of the total,13 27–34 1 was from Oromia,35 5 (15.15%) from Addis Ababa city administration,10 14 36–38 3 (9.09%) were from Harari region,39–41 3 (9.09%) were from Tigray region,42–44 1 (3.03%) was from Afar region and45 3 (9.09) were from National data 46–48. 28 (84.85%) of the included articles were cross-sectional studies,10–13 15 23–31 33–35 37–42 44–48 and remains 5 (15.15%) were case–control studies 14 16 32 36 43…”
Section: Resultsmentioning
confidence: 99%
“…As well, 27 of the studies were institution based,10–16 24 27–33 35–46 while 6 were community-based studies 23 25 26 34 47 48. The sample size of the included studies ranged from a minimum of 124 in a study conducted in southwest Ethiopia34 and to a maximum of 12 378 in a study conducted using Demographic Health Survay (DHS) data 48.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation